2009
DOI: 10.1038/mp.2009.101
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variations of chromosome 16p13.1 region associated with schizophrenia

Abstract: Deletions and reciprocal duplications of the chromosome 16p13.1 region have recently been reported in several cases of autism and mental retardation (MR). As genomic copy number variants found in these two disorders may also associate with schizophrenia, we examined 4345 schizophrenia patients and 35 079 controls from 8 European populations for duplications and deletions at the 16p13.1 locus, using microarray data. We found a threefold excess of duplications and deletions in schizophrenia cases compared with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
198
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(207 citation statements)
references
References 45 publications
7
198
1
1
Order By: Relevance
“…21 Interestingly, the duplications have also been associated with autism, cognitive impairment 17 and schizophrenia. 23,24,30 These data combined with the findings reported in this study suggest that the duplication of the region is indeed pathogenic though the penetrance is clearly incomplete. Although the small sample size and variable expressivity preclude the definitive correlation of the size and extent of the duplication with the neuro-cognitive phenotype, we observed that all patients with duplication extending centromeric to interval II (patients 6, 7, 8 and 10) had language or motor delays along with ADHD and behavioral abnormalities while only two of the five patients (patients 4 and 9) with proximal breakpoints within interval II presented with neurocognitive issues.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…21 Interestingly, the duplications have also been associated with autism, cognitive impairment 17 and schizophrenia. 23,24,30 These data combined with the findings reported in this study suggest that the duplication of the region is indeed pathogenic though the penetrance is clearly incomplete. Although the small sample size and variable expressivity preclude the definitive correlation of the size and extent of the duplication with the neuro-cognitive phenotype, we observed that all patients with duplication extending centromeric to interval II (patients 6, 7, 8 and 10) had language or motor delays along with ADHD and behavioral abnormalities while only two of the five patients (patients 4 and 9) with proximal breakpoints within interval II presented with neurocognitive issues.…”
Section: Discussionsupporting
confidence: 71%
“…The fact that region of 16p13.11 centromeric to interval II is gene poor and that significant neuropsychiatric manifestations have been previously documented with duplications involving intervals I and II imply that this is the critical region responsible for these features. 14,17,23 Ullman et al 17 had previously hypothesized that duplications that are paternally transmitted are benign while the maternal transmission leads to clinical manifestations. However, there are no known or predicted imprinted genes in the region (http://www.geneimprint.com/site/genes-by-species).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S1). One ohnolog, MYH11, is thought to carry the risk of developing aortic dissection in patients with 16p13.11 duplications (44), whereas NDE1, also an ohnolog, is the strongest candidate for neurodevelopmental phenotypes associated with CNVs at this locus (45,46). Two other ohnologs within the critical region, ABCC1 and ABCC6, encode the multidrug resistance-associated proteins 1 and 6.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, CNVs can change the dosage of one or more genes in the regions covered affects the NRXN1 gene [35][36][37][38][39][40][41][42] , and 7p36.3 dup only affects the VIPR2 gene [38,43,44] . CNVs that alter the expression of multiple genes include 1q21.1 del/dup (34 genes) [36][37][38][39]41,[45][46][47] , 3q29del/dup (21 genes) [38][39][40]44,48,49] , 15q13.3del (12 genes) [38,39,44,46,47,49] , 16p13.1dup (11 genes) [40,41,50,51] , and 22q11.2del/dup (53 genes) [38,39,44,46,47,[51][52][53][54][55][56] , etc. (see Table 2 for more details).…”
Section: Copy-number Variations and Sczmentioning
confidence: 99%